2013
DOI: 10.1016/j.celrep.2012.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic Acid Is a Tissue-Specific Proteasome Inhibitor In Vitro and In Vivo

Abstract: Gambogic acid (GA) is a natural compound derived from Chinese herbs that has been approved by the Chinese Food and Drug Administration for clinical trials in cancer patients; however, its molecular targets have not been thoroughly studied. Here, we report that GA inhibits tumor proteasome activity, with potency comparable to bortezomib but much less toxicity. First, GA acts as a prodrug and only gains proteasome-inhibitory function after being metabolized by intracellular CYP2E1. Second, GA-induced proteasome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 24 publications
4
72
0
Order By: Relevance
“…The Garcinia genus of tropical plants has yielded a structurally intriguing family of xanthone-derived natural compounds collectively referred to as caged Garcinia xanthones (CGXs) (5). Gambogic acid, the archetype of this family, inhibits tumor growth in various animal models with minimal side effects and little toxicity on immune and hemopoietic systems (6,7). Its anticancer activity has been associated with mitochondrial membrane polarization, inhibition of the B-cell lymphoma 2 (Bcl-2) family of proteins, accumulation of reactive oxygen species (ROS), suppression the NF-κB signaling pathway, and inhibition of proteasome activity (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Garcinia genus of tropical plants has yielded a structurally intriguing family of xanthone-derived natural compounds collectively referred to as caged Garcinia xanthones (CGXs) (5). Gambogic acid, the archetype of this family, inhibits tumor growth in various animal models with minimal side effects and little toxicity on immune and hemopoietic systems (6,7). Its anticancer activity has been associated with mitochondrial membrane polarization, inhibition of the B-cell lymphoma 2 (Bcl-2) family of proteins, accumulation of reactive oxygen species (ROS), suppression the NF-κB signaling pathway, and inhibition of proteasome activity (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Gambogic acid, the archetype of this family, inhibits tumor growth in various animal models with minimal side effects and little toxicity on immune and hemopoietic systems (6,7). Its anticancer activity has been associated with mitochondrial membrane polarization, inhibition of the B-cell lymphoma 2 (Bcl-2) family of proteins, accumulation of reactive oxygen species (ROS), suppression the NF-κB signaling pathway, and inhibition of proteasome activity (4)(5)(6)(7)(8)(9)(10). In previous studies, we determined that cluvenone (CLV) is the pharmacophoric structure of CGX (8,9).…”
mentioning
confidence: 99%
“…However, its molecular targets have not been thoroughly studied. Liu's group [76] reported that GA inhibits tumor proteasome activity, with potency comparable to bortezomib, the first proteasome inhibitor approved for the treatment of multiple myeloma, but with less toxicity. Their results showed that GA gains the proteasomeinhibitory function after being metabolized by intracellular CYP2E1, that GA induced proteasome inhibition is a prerequisite for its cytotoxicity and anticancer action without off-target effects, and that the expression of the CYP2E1 gene is very high in tumor tissues but low in many normal tissues, and thus GA can produce tissue-specific proteasome inhibition and tumor-specific toxicity (Figure 2).…”
Section: Gambogic Acidmentioning
confidence: 99%
“…Huang-Qin (Scutellaria baicalensis Georgi), one of the 50 fundamental herbs used in traditional Chinese medicine, is rich in flavonoids including wogonin (5,7-dihydroxy-8- Figure 2 A schematic illustration of the mechanism for gambogic acid to induce cytotoxicity of cancer cells [76,77]. methoxy-2-phenyl-4H-chromen-4-one) [78][79][80].…”
Section: Wogonin and Wogonosidementioning
confidence: 99%
“…13 GA has been approved by the Chinese Food and Drug Administration for clinical trials in cancer patients. 14 In addition, it is reported that GA mediates a wide variety of functional antitumor effects, including the induction of cell apoptosis, inhibition of proliferation, and prevention of cancer metastasis and angiogenesis. Hence, previous investigations suggest that GA might be an effective anticancer drug candidate with low toxicity to normal cells.…”
mentioning
confidence: 99%